Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Let raju's present age = x years then rohan's present age =( x+9) years 10 years ago raju's age =( x-10) years In 10 years rohan's age = x+9+10 = x+19 But as per sum: x+19 = 2(x-10) x+19 = 2x-20 2x-x = 20+19 x = 39 Therefore present age of raju = 39 years present age of rohan = 48 years

Let the age of Raju be x years. Then, Age of Rohan = (x+9) years. Now, Age of Raju 10 years ago = (x-10)years. After 10 years, Rohan's age = (x+19) years. But according to Question, Rohan's age = 2(x-10). Therefore, ⇒2(x-10)=x+19 ⇒2x-20=x+19 ⇒x=39 Therefore, Age of Raju = 39 years. Age of Rohan = 39+9 = 48 years. Ans.